Changes in Bone Marrow Adipose Tissue One Year After Roux‐en‐Y Gastric Bypass: A Prospective Cohort Study. (7th August 2019) - Blom‐Høgestøl, Ingvild Kristine; Mala, Tom; Kristinsson, Jon A; Hauge, Ellen‐Margrethe; Brunborg, Cathrine; Gulseth, Hanne Løvdal; Eriksen, Erik Fink
ABSTRACT: Bone marrow adipose tissue (BMAT) has been postulated to mediate skeletal fragility in type 2 diabetes (T2D) and obesity. Roux‐en‐Y gastric bypass (RYGB) induces a substantial weight loss and resolution of comorbidities. However, the procedure induces increased bone turnover and fracture rates. No previous study has evaluated biopsy‐measured BMAT fraction preoperatively and after RYGB. In this study, we aimed to investigate BMAT fraction of the hip in participants with and without T2D preoperatively and 1 year after RYGB and explore factors associated with BMAT change. Patients with morbid obesity scheduled for RYGB were examined preoperatively and 1 year after RYGB. Forty‐four participants were included and preoperative examinations were possible in 35. Of these, 33 (94%) met for follow‐up, 2 were excluded, and BMAT estimation was not possible in 1. Eighteen (60%) of the participants were females and 11 (37%) had T2D. Preoperative BMAT fraction was positively associated with glycosylated hemoglobin and negatively associated with areal bone mineral density (aBMD). After RYGB, BMAT fraction decreased from 40.4 ± 1.7% to 35.6 ± 12.8%, p  = 0.042, or with mean percent change of 10.7% of preoperative BMAT fraction. Change in BMAT fraction was positively associated with change in body mass index (BMI) and total body fat. In females, we observed a mean percent reduction of 22.4 ± 19.6%, whereas in males BMAT increased with a mean percent of 6.8 ± 37.5%, p  = 0.009. For males, changes in estradiol were associated with BMAT change; this was not observed for females. In participants with and without T2D, the mean percent BMAT reduction was 5.8 ± 36.9% and 13.5 ± 28.0%, respectively, p  = 0.52. We conclude that a high BMAT seems to be associated with lower aBMD and poorer glycemic control in obese subjects. After RYGB, we observed a significant decrease in BMAT. The reduction in BMAT did not differ between participants with and without T2D, but appeared sex specific. © 2019 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals, Inc.